Pengaruh Metode Ekstraksi Maceration Vortex Technique terhadap Kadar Total Flavonoid pada Daun Kersen (Muntingia calabura L.) - Ramadhani, Disty Shintya; Parbuntari, Hesty (TSAQOFAH, 2025)
Muntingia calabura L. is a neotropical plant widely recognized in traditional medicine due to its bioactive compounds, including flavonoids, alkaloids, steroids, and phenolics, which exhibit various biological activities such as antioxidant, anticancer, antimicrobial, and anti-inflammatory effects. This study aims to compare the effectiveness of the Maceration Vortex Technique and conventional maceration in extracting flavonoid compounds and total flavonoid content from M. calabura leaves. Two extraction methods were employed: the Maceration Vortex Technique, which involves soaking with shaker agitation for 2 hours followed by vortexing for 5 minutes and then standing for 72 hours; and conventional maceration, which involves soaking at room temperature for 72 hours without agitation. The results indicate that extracts obtained using the Maceration Vortex Technique contain higher total flavonoid levels compared to those produced through conventional maceration. These findings suggest that the inclusion of agitation during the extraction process enhances the efficiency of flavonoid compound recovery from M. calabura leaves.